Pengaruh Ketergantungan Media Sosial Instagram Terhadap Kesehatan Mental Mahasiswa - Migel Alfanzah Harahap; Enggar Dwi Laksono; Maryam Koria; Nafida Hetty Marhaeni (CV. ITTC INDONESIA, 2022)
Instagram is a social network application based on photos and videos. However, overusing Instagram can influence its users’ mental health. Therefore, this research aims to dive into whether or not Instagram’s dependency that affects the mental health aspect occurs in FIKOMM UMBY students. The population in this research is Communication Science Department, Universitas Mercu Buana Yogyakarta batch 2021, with as many as 266 students. Meanwhile, the researcher uses Krejie and Morgan technique to obtain 145 students as the sample. The instrument used is a questionnaire on Instagram’s dependency towards mental health, which the writers have already modified. This research is classified as a quantitative one. The data gathered is then analyzed by using SPSS software. In the end, the result illuminates that there is indeed a high dependency between Instagram and the FIKOMM UMBY students. The approximate level of dependency is as much as 26,2%; thus, the other 83,8% is influenced by further factors.